"Phytochemical Evaluation and Bioactivity of Calendula officinalis Petals: In Vitro Assessment of Antioxidant and Anti-inflammatory Effect”. - Gupta, Naincy; Chobey, Ankur; Gupta, Naveen; Rajput, Dharmendra; singh, Saumya (Journal of Neonatal Surgery, 2025)
Background: Medicinal plants have long been used as dietary supplements due to their ability to reduce inflammation and provide antioxidant benefits by neutralizing free radicals. Inflammation is a vital component of the innate immune response, acting as a protective mechanism against tissue damage caused by various harmful stimuli. Traditional remedies possess significant therapeutic properties, making them promising candidates for further scientific investigation and potential pharmaceutical development. Aim: The present investigation sought to elucidate the in vitro antioxidant and anti-inflammatory potentials of the ethanolic extract of Calendula officinalis petals, obtained through Soxhlet extraction, in order to validate its therapeutic relevance. Materials and methods: Dried and pulverized petals of C. officinalis were exhaustively extracted with 95% ethanol using the Soxhlet apparatus. The resultant extract was concentrated under reduced pressure and evaluated for bioactivity. Antioxidant capacity was quantified via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, while anti-inflammatory potential was assessed by inhibition of protein denaturation and anti-proteinase activity. Radical scavenging activity (%) and percentage inhibition were calculated spectrophotometrically. Data were analyzed statistically, and p < 0.05 was considered significant. Results and Discussion: The ethanolic extract of C. officinalis demonstrated pronounced concentration-dependent bioactivity. Antioxidant analysis revealed maximal radical scavenging activity of 85% at 20 µL, which subsequently declined at higher concentrations, suggesting an optimal efficacy range. Anti-inflammatory evaluation indicated progressive inhibition of protein denaturation and proteolytic activity, with maximal inhibition (80%) observed at 50 µL. Across all tested concentrations, the extract significantly outperformed the control (p < 0.05). The observed effects can be attributed to its phytochemical repertoire, particularly flavonoids, triterpenoids, carotenoids, and phenolic acids, which are known to mediate hydrogen atom transfer, stabilize protein conformations, and modulate pro-inflammatory pathways. Conclusion: The Soxhlet-extracted ethanolic fraction of C. officinalis exhibited dual antioxidant and anti-inflammatory activities of considerable magnitude, thereby corroborating its ethno pharmacological use. These findings underscore its potential as a phyto therapeutic candidate. Future studies should emphasize extract standardization, identification of bioactive markers, and translational validation through in vivo and clinical investigations